Usability-based Language for Authoring NCL Documents - Terças, Lucas de Macêdo; Moraes, Daniel de Sousa; Ribeiro, Dalai dos Santos; M. Neto, Manoel Carvalho; Soares Neto, Carlos de Salles (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
NCL (Nested Context Language) is a notation for hypermedia application authoring, designed to facilitate the modeling and authoring of Digital TV applications for authors with different levels of programming knowledge. However, the ease of use of NCL is questionable due to XML notation and has been the subject of study of several works that analyze its usability while proposing other solutions. This work presents sNCL (simpler NCL), a declarative domain specific language, projected using guidelines established by the CDN (Cognitive Dimensions of Notation) framework applied to NCL. To validate the proposal, an experiment with a questionnaire on the success factors in NCL and sNCL is applied to users with experience in authoring with NCL, comparing their opinions on both languages. The experiment demonstrates that sNCL gains in usability, which can improve, therefore, the performance of authors in the development of applications.